Work-Life Balance or Work-Life Integration? Case Study of Furniture Industry Employees in Cirebon Regency, West Java, Indonesia - Dwiki Fatur Rizki (Riviera Publishing, 2025)
Work-life balance (WLB) and work-life integration (WLI) are important issues in the modern world of work, especially in the furniture industry, which has high production demands and limited work flexibility. This study explores how employees at Agung Jaya Putra Furniture, Cirebon Regency, West Java, balance or integrate work with their personal lives. This research uses a qualitative approach with in-depth interviews and observation methods to understand the factors influencing the election of intermediate employees at WLB And WLI. Research shows that most employees experience difficulties implementing WLB due to long working hours and high production pressure. As a result, many are simultaneously adopting the WLI approach as an adaptive solution to managing work and personal life. However, the WLI approach also has challenges, especially regarding blurring the boundaries between work and personal life, which can lead to burnout and stress. Some employees benefit from flexibility, while others complain about the lack of rest time and social life. This study confirms that there is no universal solution for all employees because individual factors and the work environment influence preferences for WLB or WLI. Academically, this research contributes to understanding work-life balance and integration in a high-demand industry. From a practical perspective, companies are advised to consider more flexible policies to improve workforce welfare. Further studies with a broader scope are needed to understand the dynamics of WLB and WLI in various industrial sectors.